Influência da distância inter-pilar e tipos de fibras de reforço na resistência à fratura de próteses adesivas indiretas - Barbosa, Liliane Minglini (2008)
This study evaluated the fracture strength of fiber-reinforced composite inlay fixed partial dentures according to the pontic distance and the type of fiberreinforcement. One hundred and twenty bovine incisors were selected and grounded with 600-grit silicon paper to get an incisor platform, simulating a human molar incisal surface. The teeth were included in polystyrene resin blocks and the periodontal ligament was simulated with polyether material in pairs with 2 different distances: d11- 11.0 mm of pontic distance and d18- 18.0 mm of pontic distance. Teeth were prepared, resulting in incisal-distal and incisal-mesial Class II boxes. Then, samples were restored with a standardized composite inlay adhesive fixed partial denture (AFPD) made in laboratory resin (Sinfony, 3M Espe), generating 4 groups: Int- direct fiber-reinforcement (Interlig, Angelus); FiLab- laboratory unidirectional fiber-glass bundle (Fibrex Medial) associated to a laboratory multidirectional fiber-glass bundle (Fibrex Junciona l, Lab Fibrex, Angelus); and FiPon- laboratory unidirectional fiber-glass bundle associated with pre-manufactured fiber-glass pontic (Fibrex Pontic, Angelus). The AFPD samples were fixed with dual-cure resin cement (Rely-X ARC) and after 24 hours were submitted to a mechanical testing machine with a compressive axial load at the center of the pontic, with a crosshead-speed of 0.5mm/minute. Fracture modes were classified according to 3 categories. Data were analyzed by two-way ANOVA and Tukey test (P <.05). The analysis revealed that the fiber-reinforcement (P <.001) and pontic distance (P <.001) were significant. The failures were most prevalent among resin and fiber, in absence of fractures of the fibers or dental structure. The mean fracture strength and standard deviation of the AFPDs groups were: d11: FiPon (681,8 ± 268,9 ), FiLab (537 ± 186,7), Int (370,4 ± 155,8) for d18: FiPon (939,4 ± 175,6), FiLab (666,1 ± 95,5) e Int (445,8 ± 49,7). The fracture strength was significantly higher in the 18.0 mm distance with FiPon. Use of unidirectional fiber-glass bundle associated with fiber-glass pontic increases the fracture resistance irrespective of the distances tested.